ANALISIS KEMAMPUAN PEMROSESAN INFORMASI DAN DATA DIGITAL PADA KETERAMPILAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Dwiyasa, Arnelia; Kumala, Farida Nur; Andriani, Kiki Fauziah (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
Digital technology in the 21st century is growing rapidly, especially at the elementary school level. But in reality some students have not been able to adapt to technology and minimal digital literacy skills. As a result, students have difficulty in choosing valid information on digital media. Therefore, students must have digital information and data processing skills. These skills are needed to filter information and data obtained using digital technology in order to be able to analyze information from digital sources accurately and can be justified. This study aims to determine the level of digital data and information processing ability in digital literacy skills of elementary school students. This study uses a descriptive quantitative approach with a survey method, with data collection through questionnaires and online case study test questions to a sample of 151 high school elementary school students. The data analysis technique used in this research is descriptive statistical technique. The results of this study indicate that the ability to process information and digital data on digital literacy skills of students from 4 elementary schools in East Java is still in the sufficient category, so it still needs to be improved.